2023
DOI: 10.1021/acschembio.3c00092
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescence Polarization Assay for Macrodomains Facilitates the Identification of Potent Inhibitors of the SARS-CoV-2 Macrodomain

Abstract: Viral macrodomains, which can bind to and/or hydrolyze adenine diphosphate ribose (ADP-ribose or ADPr) from proteins, have been suggested to counteract host immune response and be viable targets for the development of antiviral drugs. Therefore, developing high-throughput screening (HTS) techniques for macrodomain inhibitors is of great interest. Herein, using a novel tracer TAMRA-ADPr, an ADP-ribose compound conjugated with tetramethylrhodamine, we developed a robust fluorescence polarization assay for variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 29 publications
(51 reference statements)
1
14
0
Order By: Relevance
“…The IC 50 of isoADPr (Figure 3B) was calculated from the FP binding curve to be 623 nM, which is comparable to the reported K d value of 370 nM. In our previous study on FP assay for macrodomains, 16 we found the ADPr-N 3 precursor is more potent than ADPr for SARS-CoV-2 Macro1. Here, we also tested the 3′-azido-isoADPr precursor and found it is 2fold more potent than isoADPr for RNF146 WWE.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The IC 50 of isoADPr (Figure 3B) was calculated from the FP binding curve to be 623 nM, which is comparable to the reported K d value of 370 nM. In our previous study on FP assay for macrodomains, 16 we found the ADPr-N 3 precursor is more potent than ADPr for SARS-CoV-2 Macro1. Here, we also tested the 3′-azido-isoADPr precursor and found it is 2fold more potent than isoADPr for RNF146 WWE.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
“…It should be noted that significant amounts of 3′-azido-AMP and monophosphorylated byproducts were also formed, and normal-phase purification in the water–ammonia–isopropanol system was conducted to achieve good separation. Finally, click reaction of 9 with the previously reported TAMRA-alkyne furnished the target molecule TAMRA-isoADPr ( 10 ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures and assay conditions were previously described . mP values were calculated using the equation below: mP = F / / G * F F / / + G * F × 1000 where F // and F ⊥ are the parallel and perpendicular fluorescence intensities, respectively, and G is the grating factor of the instrument, which was calibrated so that 20 nM 5-TAMRA in water has an mP shift of 50.…”
Section: Methodsmentioning
confidence: 99%
“…The general procedure and assay conditions were same as previously described . The final protein and tracer concentrations for different protein–tracer pairs used in this study are listed in Table .…”
Section: Methodsmentioning
confidence: 99%